2019
DOI: 10.1128/jcm.01711-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accelerate Pheno System for Identification of Acinetobacter Clinical Isolates and Minocycline Susceptibility Testing

Abstract: The Accelerate Pheno system (AXDX) is a rapid phenotypic bacterial identification and susceptibility testing system which is approved for use with positive blood cultures. Acinetobacter baumannii is a nosocomial pathogen for which the limited treatment options include minocycline in the case of multidrug resistance. Here, we studied the performance of A. baumannii identification and minocycline susceptibility testing by AXDX using 101 contemporary Acinetobacter sp. clinical isolates. Overall, the sensitivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Studies using the APS assay have reported pathogen identification sensitivities ranging from 91.2% to 100% and specificities ranging from 97.3% to 100% for organisms on the panel. 45 , 48 , 49 , 50 , 51 , 52 , 53 , 54 However, 1 study reported an overall false-positive rate as high as 9.5%, of which 42.1% is mitigated by having prior negative Gram stain. 45 Therefore, confirmatory Gram stain should be performed before performing the APS assay.…”
Section: Rapid Direct Phenotypic Antimicrobial Susceptibility Testimentioning
confidence: 98%
See 1 more Smart Citation
“…Studies using the APS assay have reported pathogen identification sensitivities ranging from 91.2% to 100% and specificities ranging from 97.3% to 100% for organisms on the panel. 45 , 48 , 49 , 50 , 51 , 52 , 53 , 54 However, 1 study reported an overall false-positive rate as high as 9.5%, of which 42.1% is mitigated by having prior negative Gram stain. 45 Therefore, confirmatory Gram stain should be performed before performing the APS assay.…”
Section: Rapid Direct Phenotypic Antimicrobial Susceptibility Testimentioning
confidence: 98%
“…Importantly, lower CA values have been observed for Pseudomonas species and Acinetobacter species. 48 , 52 , 55 Because assay performance varies depending on the pathogen, laboratories should decide on which organisms to perform the APS assay to best complement existing techniques and improve resulting times. Although this assay has high sensitivity for target organisms, in 1 study only 58.1% to 88.7% of clinical samples analyzed by this assay received any pathogen identification.…”
Section: Rapid Direct Phenotypic Antimicrobial Susceptibility Testimentioning
confidence: 99%